Evaluation of Dependence between Left Atrial Appendage Flow Velocity Examined in Transoesophageal Echocardiography (TTE) and CHA2DS2-Vasc Score in Patients with Atrial Fibrillation (AF) - Szponar, Jaroslaw; Krajewska, Anna; Tchórz, Michal; Danielewicz, Piotr; Kujawa, Anna; Górska, Agnieszka; Slomka, Tomasz (Archives of Clinical and Biomedical Research, 2022)
Objectives: The objective of the paper was evaluation of link between 1) left atrial appendage flow velocity (LAA) in patients with Atrial Fibrillation (AF) examined during transoesophageal echocardiography and 2) CHA2DS2-VASc score obtained by the patient. Methods and results: There were 450 people examined (N=450). Transoesophageal echocardiography with doppler sample placed 1 centimetre below LAA ostium was performed in all the patients. Pulse Wave doppler technique (PW) was used. It was determined that there is a key dependence between examined features (p=0,012). The content is weak and negative though. Left atrial appendage flow Velocity (V) is expected to be lower for each next class. Conclusions: The dependence between two parameters (the left atrial appendage flow velocity and the points in CHA2DS2-VASc score) was indicated. In future it may be possible to use the left atrial appendage flow velocity as a new factor qualifying patients for oral anticoagulation therapy.